(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2025)
This study investigates the role of digital distrust as a determinant of online transaction acceptance among adults in Cross River State, Nigeria, a region characterized by growing internet penetration yet persistent skepticism toward digital platforms. Digital distrust, encompassing fears of privacy breaches, fraud, and system unreliability, is hypothesized to significantly hinder the adoption of online transactions. Using a primary data collection method, a structured questionnaire was administered to 400 adults aged 18–60 across urban and rural areas of Cross River State. The study employs the Technology Acceptance Model (TAM) extended with digital distrust as a theoretical framework. Descriptive statistics, correlation analysis, and multiple regression were used to analyze the data. Findings reveal that digital distrust negatively impacts perceived usefulness (β = -0.42, p < 0.01) and perceived ease of use (β = -0.38, p < 0.01), subsequently reducing behavioral intention to use online transactions (R² = 0.56). Notably, 68% of respondents expressed concerns about data security, with rural participants exhibiting higher distrust levels (mean = 4.12) than urban counterparts (mean = 3.45). The study highlights the mediating role of trust-building mechanisms, such as transparent policies and digital literacy programs, in mitigating distrust. Recommendations include targeted interventions by policymakers and e-commerce platforms to enhance trust through education and robust security measures. This research contributes to understanding contextual barriers to digital adoption in developing economies